2017
DOI: 10.1590/1807-3107bor-2017.vol31.0068
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and coating stability evaluation of nickel-titanium orthodontic esthetic wires: an in vivo study

Abstract: The objective of this study was to compare coating dimensions and surface characteristics of two different esthetic covered nickel-titanium orthodontic rectangular archwires, as-received from the manufacturer and after oral exposure. The study was designed for comparative purposes. Both archwires, as-received from the manufacturer, were observed using a stereomicroscope to measure coating thickness and inner metallic dimensions. The wires were also exposed to oral environment in 11 orthodontic active patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…An electrochemical characteristic study of PTFE coated NiTi orthodontic wires also supported the finding that the PTFE coated archwires, which were immersed in artificial saliva under a low pH (pH 4), demonstrated lower corrosion rates and passive current densities than uncoated NiTi substrates because of electrolyte penetration in the pore of the PTFE deposits ( Mareci et al, 2015 ). However, this is inconsistent with a previous study that reported that the PTFE coating had poor stability due to thinner coating layer of the as-received PTFE coated aesthetic archwires than what was reported by the manufacturer ( Argalji et al, 2017 ). Another study also reported that PTFE coated archwires showed the highest surface roughness after 28 days of immersion in artificial saliva with pH 6.75 when compared to epoxy resin ( Muayad and Ghaib, 2017 ).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…An electrochemical characteristic study of PTFE coated NiTi orthodontic wires also supported the finding that the PTFE coated archwires, which were immersed in artificial saliva under a low pH (pH 4), demonstrated lower corrosion rates and passive current densities than uncoated NiTi substrates because of electrolyte penetration in the pore of the PTFE deposits ( Mareci et al, 2015 ). However, this is inconsistent with a previous study that reported that the PTFE coating had poor stability due to thinner coating layer of the as-received PTFE coated aesthetic archwires than what was reported by the manufacturer ( Argalji et al, 2017 ). Another study also reported that PTFE coated archwires showed the highest surface roughness after 28 days of immersion in artificial saliva with pH 6.75 when compared to epoxy resin ( Muayad and Ghaib, 2017 ).…”
Section: Discussioncontrasting
confidence: 94%
“…Clinically, commercially-available coated archwires have demonstrated partial or full coating loss after as few as 21 to 28 days of intraoral exposure ( Argalji et al, 2017 , Ulhaq et al, 2017 ). These losses are noticeable and leave patients feeling dissatisfied ( Bradley et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then many researchers have studied the esthetic archwires evaluating the clinical performance in vivo and in vitro . [21019202122]…”
Section: Discussionmentioning
confidence: 99%
“…Archwires with uniformly thicker coatings demonstrated better properties than the thinner coated archwires. [10]…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, esthetic brackets and wires have been widely studied, tested and compared in terms of their coefficient of friction, 16 surface roughness, 17 , 18 mechanical properties 17 and esthetic stability during treatment. 12 , 18 , 19 Their advantages and disadvantages have already been described in numerous studies in the literature. 7 , 12 - 14 , 17 Recently, Pinzan-Vercelino et al 21 performed a cross-sectional study to evaluate laypersons’ esthetic perceptions of metal archwires with and without esthetic coating and found that the epoxy resin wire was the most esthetic.…”
Section: Introductionmentioning
confidence: 99%